CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

If f(x) = x2 + 1 and g(x) = x - 1, then fog(3) =.

A
6
No worries! We‘ve got your back. Try BYJU‘S free classes today!
B
5
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
C
7
No worries! We‘ve got your back. Try BYJU‘S free classes today!
Open in App
Solution

The correct option is B 5
f(x) = x2 + 1, g(x) = x - 1
fog(x) = f{g(x)}
fog(x) = f{x - 1}
fog(x) = (x1)2+1
fog(x) = x2 - 2x + 1 + 1
fog(x) = x2 - 2x + 2
So, fog(3) = 32 - 2(3) + 2
fog(3) = 9 - 6 + 2
fog(3) = 5

flag
Suggest Corrections
thumbs-up
0
BNAT
mid-banner-image